Research on the operational reliability system control methodology and its application for aerospace mechanism. (24th November 2016) - Gao, Xin; Wu, Haoxin; Du, Mingtao; Chen, Gang; Sun, Hanxu; Jia, Qingxuan; Wang, Yifan
According to the characteristics of space missions and space environment, to slow performance deterioration and possible reliability attenuation for aerospace mechanisms, an operational reliability system control methodology is proposed in this article. A space manipulator – a kind of typical complicated aerospace mechanism – is chosen as the research object. First, considering relevant materials and structure mechanism of joint and link parts, the influence factors of operational reliability for space manipulator are divided. Then, by introducing the responding layer factors, a mapping relationship between the influence factors of operational reliability and control variables is analysed. On this basis, a new method to build a hierarchical control system of operational reliability for the aerospace mechanisms is proposed. In this method, the mechanism how the influence factors of operational reliability are introduced into the control system is defined, and an operational reliability system control model is built, which is made up of task planning, path planning, and motion control. Finally, the proposed methodology is further explained with the operational stability of a space manipulator as an example. After analysing the mapping relationship among the influence factors of operational reliability, the factors of responding layer and control variables, a multi-objective optimization method based on Nondominated Sorting Genetic Algorithm II (NSGA-II) is proposed to ensure the operation stability for a space manipulator. These optimization objectives are introduced into the optimized control model at path planning level as constraints. According to these constraints, the optimized control system can be adjusted to improve the operation stability of the manipulator, and the operational reliability is also improved during this process correspondingly. Simulation results prove the effectiveness of the proposed method.